Effect of fascial closure using barbed sutures on incisional hernias in midline laparotomy for gynecological diseases: A multicenter randomized controlled trial (KGOG 4001) - Yong Jae Lee; Nam Kyeong Kim; Kidong Kim; Chel Hun Choi; Keun Ho Lee; Jong-Min Lee; Kwang Beom Lee; Dong Hoon Suh; Sunghoon Kim; Min Kyu Kim; Seok Ju Seong; Myong Cheol Lim (PLoS ONE, 2025)
Objective To identify the effect of fascial closure using barbed sutures on the incidence of incisional hernia in patients undergoing elective midline laparotomy for gynecological diseases. Methods In this multicenter, non-blind randomized controlled trial conducted from February to December 2021, patients with a BMI < 35 kg/m 2 and aged >18 years, scheduled for midline laparotomy, were randomly assigned to receive either barbed (experimental) or non-barbed sutures (control) for fascial closure. The primary outcome was the cumulative incidence rate of incisional hernia up to 1-year post-surgery. Secondary outcomes included incisional hernia up to 2-years post-surgery, wound complications, and postoperative pain assessed by Brief Pain Inventory-Korean scores, and Numeric Rating Scale. Results Out of 174 patients (experimental, 86; control, 88), 36 were excluded due to dropout or loss to follow-up, leaving 138 patients (experimental, 67; control, 71) included in the analysis. The groups were balanced in terms of cancer surgeries, mean wound length, and mean surgery time. The cumulative incidence rates of incisional hernia up to 1-year (0.0% vs. 1.4%; p > 0.999) and 2-years (0.0% vs. 3.4%, p = 0.496) post-surgery did not differ significantly between the experimental and control groups. Additionally, no significant differences were observed in the incidence of wound dehiscence 4 weeks post-surgery, cumulative incidences of wound dehiscence and wound infection up to 4 weeks post-surgery, or postoperative pain scores between the groups. Conclusions Fascial closure using barbed sutures resulted in no cases of incisional hernia up to 2-years post-surgery, but did not demonstrate a significant reduction in incisional hernia rates compared with the non-barbed suture. Trial registration ClinicalTrials.gov NCT04643197